Aerosol remote sensing over the ocean using MSG-SEVIRI visible images - Bennouna, Y. S.; de Leeuw, G.; Piazzola, J.; Kusmierczyk-Michulec, J. (Journal of Geophysical Research. B. Solid Earth, 2009)
With its observational frequency of 15 minutes, the Meteosat Second Generation (MSG) geostationary satellite offers a great potential to monitor aerosol transport using Spinning Enhanced Visible and Infra‐Red Imager (SEVIRI) data. To explore this potential, an algorithm for the retrieval of aerosol optical properties has been developed for use over the ocean. It is a multispectral algorithm based on the single‐view algorithm for the Along Track Scanning Radiometer (ATSR‐2) (Veefkind and de Leeuw, 1998) which has been adapted to the corresponding channels of SEVIRI (635 nm, 810 nm and 1640 nm). The SEVIRI Aerosol Retrieval Algorithm (SARA) provides the Aerosol Optical Depth (AOD) for these channels. To illustrate its capabilities, the application of this algorithm to two cases is presented: (1) a forest‐fire smoke plume advected from Spain and Portugal over the Atlantic Ocean in August 2006, and (2) an outbreak of Saharan dust over the Western Mediterranean Sea in February 2006. The results obtained are validated with AERONET ground‐based measurements for two coastal stations, and compared with the retrievals from the Moderate Resolution Imaging Spectroradiometer (MODIS) on NASA's Terra and Aqua satellites. The diurnal variations of the aerosol optical depth observed at the AERONET sites are well reproduced, and the spatial patterns retrieved using the SARA algorithm are in reasonable agreement with those observed by MODIS.